2005
DOI: 10.1021/ja0535662
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Magnetooptical Effects Caused by Piezoelectric Ferromagnetism in F4̄3m-type Prussian Blue Analogues

Abstract: The second harmonic generation (SHG) and magnetization-induced SHG (MSHG) of AMA[MB(CN)6]-type (F3m) Prussian blue analogues (i.e., CsCo[Cr(CN)6].0.5H2O and RbMn[Fe(CN)6]) were observed. A large interaction between the nonlinear optical response and magnetic spins was observed in CsCo[Cr(CN)6].0.5H2O. These observations of SHG and MSHG imply that AMA[MB(CN)6]-type Prussian blue analogues are piezoelectric above the Curie temperature (TC) and piezoelectric ferromagnet below TC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 37 publications
3
81
0
Order By: Relevance
“…Examples of the first approach have given rise to the combination of magnetism and conductivity, or even superconductivity, in the same crystal, 10,11 whereas examples of the second approach can be found in the so-called spin-crossover complexes with a LIESST effect, 12 or in Prussian Blue Analogues (PBAs) with photomagnetism (LIESST effect), 13 or piezomagnetism. 14 In this case, the magnetism is coupled with light or pressure in such a way that by applying the corresponding external stimulus (light irradiation or pressure) the spin state can be tuned. There are several reasons that justify the extension of this approach to the field of MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the first approach have given rise to the combination of magnetism and conductivity, or even superconductivity, in the same crystal, 10,11 whereas examples of the second approach can be found in the so-called spin-crossover complexes with a LIESST effect, 12 or in Prussian Blue Analogues (PBAs) with photomagnetism (LIESST effect), 13 or piezomagnetism. 14 In this case, the magnetism is coupled with light or pressure in such a way that by applying the corresponding external stimulus (light irradiation or pressure) the spin state can be tuned. There are several reasons that justify the extension of this approach to the field of MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…For the very first time, we showed that the three‐dimensional cyanido‐bridged network can be used as a coordination scaffold to incorporate 4f metal ion, serving as a luminescent single‐molecule magnet. There findings open a new research pathway going beyond the broad scope of magnetic and optical functionalities, which has been found for the related 3D cyanido‐bridged assemblies . Moreover, the obtained networks contain symmetry‐breaking tetrahedral Cu I linkers.…”
Section: Figurementioning
confidence: 56%
“…[5] The special attention was given to three-dimensionalb imetallic coordination frameworks based on cyanide ligands, especially classical Prussian blue analogues (PBAs) built of octahedralh exacyanidometallates. [6] They exhibit variousp hysical functionalities, such as ferrimagnetism of high critical temperatures, [7] magnetic second harmonic generation (SHG), [8] charge-transfer phase transition [9] and ionic or electricalc onductivity. [10] There are also attractive platforms for switchable materials exhibiting reversiblep hotomagnetism, [11] humidity-sensitivem agnetism, [12] andp hotoswitching of the SHG polarization plane.…”
mentioning
confidence: 99%
“…[1][2][3] Among these compounds, it has been shown that Prussian-blue analogues offer many prospects in nonlinear optics. [4][5][6][7][8] For instance, the cyano-bridged coordination polymer of Rb x Mn[Fe(CN) 6 ] (x+2)/3 ·zH 2 O switches from a centrosymmetric to a non-centrosymmetric and piezoelectric structure when one increases the Rb content above x = 0.7. [6] The non-centrosymmetric structure of the compound gives rise to second-order nonlinear optical properties that are revealed by second-harmonic generation (SHG) experiments.…”
Section: Introductionmentioning
confidence: 99%